Listening to farmers' perceptions through participatory rice varietal selection: A case study in villages in Eastern Uttar Pradesh, India - Paris, T.R.; Singh, Abha; Luis, Joyce; Singh, Hari Nath; Singh, Omkar; Singh, Sinjay; Singh, Ram Kathin; Sarkarung, Surapong (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper presents a case study based on the findings in two villages in eastern Uttar Pradesh, India, part of a project started in 1997 to develop, test, and refine methodologies of participatory research and gender analysis as they apply to the development of new technologies in germplasm and natural resource management. The two villages occupy different agro ecological areas and also differ in sociocultural characteristics. Both male and female farmers were included in Ihe study, and details of their preferences for the rice varieties studied are presented in this paper.